Komparasi Produksi dan Pendapatan Usahatani Bawang Merah Antara Petani Pemilik dan Penggarap di Desa Bonto Maccini Kecamatan Sinoa Kabupaten Bantaeng - Masita Dahmiati; Ratnawati Tahir; Asriyanti Syarif (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2023)
Knowing the comparative production and income of shallot farming between owner and cultivator farmers in Bonto Maccini Village, Sinoa District, Bantaeng Regency is the aim of this research. The research was carried out from June to August 2022. The sampling method was carried out by purposive sampling with 24 owner farmers and 24 sharecroppers. The data analysis used is the t test. The results of this study indicate that the average production of shallot farming by owner farmers is 8.819 Kg/Ha/MT with an income of Rp.181.951.589/Ha/MT. Compared to the average production of shallot farming, sharecroppers are 8.415 Kg/Ha/MT with an income of Rp.173.381.456/Ha/MT. With the results of the t test analysis, it turns out that the calculated t is greater than the t table. This means that the production and income of shallot farming by owner farmers is greater than the production and income of shallot farming by sharecroppers.